Healing Through Culture for Incarcerated Aboriginal People - Hyatt, Ashley (First Peoples Child & Family Review, 2013)
Statistically, Aboriginal peoples in Canada are over represented in prisons throughout the country (Hayman, 2006; Perreault, 2009; Rymhs, 2008; Waldram, 1997). While representatives from the Canadian government recognize that the Aboriginal incarceration rates are an issue (CBC, 2013; Perreault, 2009), they have failed to find a solution. A link has been found to demonstrate how an erosion of Aboriginal culture through the legacy of residential schools has contributed to the current inflated Aboriginal incarceration statistics (Waldram, 1997). As such, cultural healing in prisons may be a crucial factor to Aboriginal inmates’ rehabilitation. Cultural healing can be implemented in prisons by: providing inmates with access to Elders, allowing Elders to perform ceremonies, providing inmates with access to sacred medicines, and increasing the number of healing lodges and sacred circles.